Biodiversity futures: digital approaches to knowledge and conservation of biological diversity - H. Freitas; H. Freitas; A. C. Gouveia; A. C. Gouveia (Web Ecology)
Biodiversity, encompassing species diversity, genetic resources, and ecosystems, is essential for human well-being and quality of life. However, the scale of human activities has significantly impacted the planet's biodiversity, with many species facing extinction in the coming decades with unknown consequences. Global commitments, such as the Aichi Biodiversity Targets and the United Nations (UN) Sustainable Development Goals, are not delivering consistent results, and progress on conservation has been frustratingly slow. With a short time frame to meet the 2030 targets of the Kunming-Montreal Global Biodiversity Framework, urgent action is needed to address the crisis. Digital technologies emerge as indispensable tools in understanding, monitoring, and conserving biodiversity. They offer multiple solutions, from remote sensing to citizens involvement mediated by science apps, providing unprecedented volumes of data and innovative tools for conservation efforts. Despite their immense potential, digital solutions raise concerns about technology and data accessibility, environmental impacts, and technical limitations, as well as the need for specialized human resources, robust collaboration networks, and effective communication strategies. This paper, drawn from discussions at the Digital with Purpose Global Summit in 2023 and 2024, held in Portugal, and complemented by expert opinion and literature, reflects on existing biodiversity-related digital technologies, identifies challenges and opportunities, and proposes steps to strengthen the nexus between technology and the biodiversity agenda. By providing science and technology stakeholders with recommendations on accelerating the role of digital technologies in biodiversity knowledge and conservation, it aims to catalyse impactful change in this critical field of devising brighter futures for biodiversity and humanity.